Carex × takhtadjanii (Carex diluta × C. distans; Cyperaceae), nov hibrid za floro Ukrajine - Peregrym, Mykyta; Koopman, Jacob (Hacquetia, 2023)
There are 96 species of the genus Carex (Cyperaceae) known in the flora of Ukraine, but so far there are no data about its hybrids for the country yet. However, the first one, C. ×takhtadjanii [C. diluta × C. distans], was discovered in Starobilsk town (Luhansk region) during a field investigation in 2021. Detailed information about this floristic finding with the description of morphological characters of this hybrid and its habitat is given in this short communication. Also a map with known locations of C. ×takhtadjanii around the world is compiled, as well as the main morphological differences between this hybrid and its parental species are reported.